Diagnostic relevance of free light chain indices and their relation to the clinical presentation of multiple sclerosis - Sanja Karakatič; Jožef Magdič; Sašo Karakatič; Tomaž Omerzu; Evgenija Modrič; Tanja Hojs Fabjan (Acta Medico-Biotechnica, 2021)
Purpose: Cerebrospinal fluid (CSF) free light chains (FLC) are of promising diagnostic importance in patients with multiple sclerosis (MS). However, research is required to confirm their utility as part of the diagnostic criteria for MS. In addition, very few publications can be found addressing the relationship of FLCs to the clinical presentation at the onset of MS. We aimed to evaluate the diagnostic performance of the FLC kappa and lambda indices, and explored their relationship to the number and type of functional systems (FS) involved.Methods: FLC indices were determined in paired CSF and serum samples from 71 patients with noninflammatory neurological diseases (non-MS, n = 29) and new-onset MS (MS, n = 42). The latter were further divided into two groups with mono- and polysymptomatic presentation. FS involvement was evaluated in accordance with the Expanded Disability Status Scale (EDSS).Results: Using both FLC indices along with the age and sex of patients, the diagnostic accuracy of MS was higher (AUC, 0.991; sensitivity, 95.5%; specificity, 95.8%) than that observed when using either the lambda index (AUC, 0.677; sensitivity, 68.0%; specificity, 60.0%) or kappa index (AUC, 0.957; sensitivity, 88.5%; specificity, 88.0%) alone. No differences were observed in the lambda (U = 78.0; p = 0.749) or kappa indices (U = 82.0; p = 0.885) between mono- and polysymptomatic patients. Nor was a correlation found between FLC indices and EDSS scores.Conslusion: FLC indices could be useful diagnostic markers for MS. However, such indices do not differentiate between clinical presentations at disease onset and are not correlated with baseline EDSS scores.